Pemberdayaan Remaja Sadar Anemia di Desa Ngemplak Kabupaten Sukoharjo : Upaya Menjaga Kesehatan dan Produktivitas Generasi Muda - Kusumaningrum, Tanjung Anitasari Indah; Almayda, Mutiara Bahi; Az-Zahra, Qoonitah; Muzakhi, Mika Tata; Indriyana, Rizka Amalia; Cahya, Annisa Dewi; Pratiwi, Puspita Intan; Rudisty, Bunga Cintantya; Soleha, Azza Rhohidatus (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service aims to raise awareness among adolescent girls and parents about the importance of iron nutrient intake through health education, the development of TTD consumption reminder tools, and encouraging routine Hb checks, with a target of reducing anemia incidence by 30% within six months. The methods used in this community service included counseling, demonstrations, and the formation of an anemia-aware youth community. Monitoring and evaluation of the activities were conducted through the distribution and checking of TTD consumption compliance cards, as well as checking Hb levels in adolescent girls. The results of this community service showed an increase in average knowledge among adolescents from 16.27 to 17.33 regarding anemia prevention behaviors, and adolescents can prepare food models according to the